Chaetomitrium Ctenidioides - Monica Suleiman; Hiroyuki Akiyama (Museum of Nature and Human Activities, 2014)
(1) Plants are very small and densely branched; (2) branches are slightly f lattened; (3) stem leaves are acute, blunt and slightly constricted below; (4) leaf margins are bluntly denticulate with geminate teeth; (5) lamina cells are spiculose-prorate above and prorate below; (6) branch leaves smaller, ca. 0.5 mm long, ovate and apices shortly acute.